2003
DOI: 10.1210/en.2002-221026
|View full text |Cite
|
Sign up to set email alerts
|

Administration of PTH-(7-84) Antagonizes the Effects of PTH-(1-84) on Bone in Rats with Moderate Renal Failure

Abstract: Circulating parathyroid hormone (PTH) is a mixture of PTH-1-84 and carboxy-terminal (C-PTH) fragments. Recently, the "intact" PTH assay was reported to detect not only PTH-(1-84) but also a C-PTH fragment, presumably PTH-(7-84). The purpose of this study was to determine whether PTH-(7-84) antagonizes the PTH-(1-84) effects on bone. Forty-eight rats were thyroparathyroidectomized (TPTX), eight were used as controls and the remaining TPTX rats (10/group) were nephrectomized (Nx) and subsequently given PTH-(1-84… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
70
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(73 citation statements)
references
References 0 publications
2
70
0
1
Order By: Relevance
“…Bears do not urinate during hibernation, and therefore may experience a similar phenomenon. Large C-PTH fragments, acting through a CPTH receptor found on osteoblasts and osteocytes, have an anti-resorptive effect in vitro and a hypocalcaemic effect in vivo [49][50][51]. A possible mechanism for how PTH could explain the cortical bone remodeling observed in the current study is shown in Figure 6.…”
Section: Discussionmentioning
confidence: 71%
“…Bears do not urinate during hibernation, and therefore may experience a similar phenomenon. Large C-PTH fragments, acting through a CPTH receptor found on osteoblasts and osteocytes, have an anti-resorptive effect in vitro and a hypocalcaemic effect in vivo [49][50][51]. A possible mechanism for how PTH could explain the cortical bone remodeling observed in the current study is shown in Figure 6.…”
Section: Discussionmentioning
confidence: 71%
“…Thus, the accumulation of PTH (7-84) in renal failure may lead to PTH resistance by internalizing and downregulating PTH receptors without their activation, having an inhibiting net effect on PTH signaling (27). In this study PTH (7-84) treatment of both cell lines frequently exerts antagonistic effects on the regulation of genes related to HA metabolism as compared with PTH (1-34).…”
Section: Discussionmentioning
confidence: 82%
“…In this study PTH (7-84) treatment of both cell lines frequently exerts antagonistic effects on the regulation of genes related to HA metabolism as compared with PTH (1-34). These actions could be due to a non-PTH (1-34)-like effect on the PTH1R, since PTH (7-84) can bind to this receptor, inhibit the action of the N-terminally intact agonists, and induce internalization in some cells (27). Alternatively, signaling of the N-terminal truncated peptides through a novel putative PTH receptor with high affinity binding site for carboxyl terminal PTH peptides has been proposed (7).…”
Section: Discussionmentioning
confidence: 99%
“…2 Vascular calcification is very severe in patients with end stage renal disease; phosphate retention and an elevated calcium-phosphate product no doubt contribute to pathophysiology (44). In this setting, however, both skeletal refractoriness to PTH and secondary hyperparathyroidism arise, the former in part because of PTH(7-84), a PTH fragment that antagonizes PTH(1-84) signaling (45). Of note, hypoparathyroidism arising from either congenital (46) or iatrogenic (47) causes appears to increase the risk for cardiovascular calcification.…”
Section: Pth(1-34) and Opn Suppress In Vitro Osteogenic Mineralizatiomentioning
confidence: 99%